Opportunities and challenges for assisting MSMEs with halal products in Sungsang Village in Banyuasin Regency as a halal tourism destination - Falahudin, Irham; Saputra, Andi; Nurseha, Tito; Rachmania, Rachmania; Jayanti, Sri Delasmi (Universitas Ahmad Dahlan, 2025)
Indonesia is one of the countries with the largest adherents of Islam in the world. Indonesia is also a country that has great potential for tourism with halal products. One of the halal tourist destinations in South Sumatra is the fishing village in Sungsang Village, Banyuasin Regency. The Fisherman's Village in the Sungsang area has been used as a tourist destination by the Banyuasin Regency Regional Government, and it has been running well in recent years. The number of domestic and foreign tourists visiting the Sungsang area has reached hundreds or thousands. The research uses quantitative descriptions of MSMEs in the Banyuasin district. The results of the SWOT analysis can be developed into three models based on potential and uniqueness, namely: a tourist village pattern based on the uniqueness of local cultural resources, namely the decorative boat tradition, a tourist village pattern based on the uniqueness of natural resources as a fishing village tourist village and a tourist village pattern based on the uniqueness of industrial creative economic activities. craft crackers and shrimp pempek. Three models of halal tourism development in Sungsang Village, Banyuasin Regency, South Sumatra are supported by several IFAS and EFAS factors with a difference of 0.62 which is positive, namely: creative industry from MSMEs that already have halal certificates for their products, the availability of adequate places of worship in each village. and the existence of annual events in the form of traditional decorative boat competitions. The development of halal tourism in Sungsang Village also has challenges, including limited facilities and infrastructure, accommodation, and transportation access to tourist destinations. not enough. Keywords: Challenges, Halal, MSMEs, Opportunities, Tourism.